Controlled Precursor Differentiation Enables Palladium-Catalyzed Divergent Carbonylation of Cyclobutenols - Yu-Kun Liu; Peng Yang; Hefei Yang; Jiajun Zhang; Xiao-Feng Wu (Journal of the American Chemical Society, 2026)
Abstract Controlling reaction selectivity is a central challenge in synthetic chemistry, particularly when multiple competing reactivity modes coexist within a single substrate. Existing strategies generally rely either on selectivity control during substrate activation or on downstream divergence from a common intermediate. However, these paradigms are less effective when distinct precursor states can independently evolve into distinct reaction manifolds. Herein, we introduce precursor differentiation as a distinct strategy for achieving divergent carbonylation. Through condition-controlled modulation of substrate evolution, a common cyclobutenol substrate can be selectively diverted into two distinct reactive precursors prior to catalytic engagement, thereby enabling access to two different carbonylation pathways. Under palladium catalysis, this strategy enables the highly selective synthesis of either hydroxyl-retained cyclobutanecarboxamides or cyclobutenamides from the same cyclobutenol platform. The method exhibits broad substrate scope (99 examples), consistently high selectivity (>20:1), and compatibility with pharmaceuticals and biologically relevant molecules. Furthermore, the resulting cyclobutenamide products serve as versatile platform intermediates for the selective synthesis of structurally distinct 3-azabicyclo[3.2.0]heptane and 3-azabicyclo[3.1.1]heptane frameworks. Mechanistic studies support a condition-controlled precursor differentiation process prior to carbonylation, providing a conceptual basis for achieving divergent carbonylation through selective control of precursor evolution.